The Influence of Zinc (Zn) Intake with Stunting Toddlers in Surakarta - Artia Happy Aprilitasari; Muwakhidah Muwakhidah (Journal of Nutraceuticals and Herbal Medicine, 2020)
Stunted growth of toddlers is caused by the disturbance in the content, lack of micronutrients, less energy intake, and infectious diseases that are caused by stunting in children aged under five years old. Preliminary study results were conducted in the city of Surakarta the highest stunting prevalence in the work area Puskesmas Penumping. Based on data of weighing results in February 2016, the highest prevalence was in Kelurahan Panularan with very short children aged 12-36 months old as many as 22 (12.71%) toddlers and short toddlers as many as 29 (16.76%) toddlers. The purpose of this research is to know the intake of zinc and calcium in stunting toddlers in Surakarta City. The results of this quantitative study using a cross-sectional approach with the number of respondents 71 toddlers obtained by proportional random sampling technique. The data of food intake was obtained through 24-hour recall interviews for three consecutive days and nutritional status data was obtained from measurement of height and weighing children. Data analysis using Independent T-Test. From the result of research known that zinc (Zn) toddler stunting and non-stunting averaging 181,43 ± 197. According to the results of a bivariate analysis, there was no difference in zinc intake with stunting and non-stunting events in children aged 12-36 months (p = 0.223).